2015
DOI: 10.1007/s11589-015-0120-5
|View full text |Cite
|
Sign up to set email alerts
|

The strain seismograms of P- and S-waves of a local event recorded by four-gauge borehole strainmeter

Abstract: At a sampling rate of 100 samples per second, the YRY-4 four-gauge borehole strainmeters (FGBS) are capable of recording transient strains caused by seismic waves such as P and S waves or strain seismograms. At such a high sampling rate, data from the YRY-4 strainmeters demonstrate fairly satisfactory self-consistency. The strain tensor seismograms demonstrate the senses of motion of P waves, that is, the type of seismic wave travels in the direction of the maximum normal strain change. The observed strain pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Unlike GTSM strainmeter such as the United States, which can produce high frequency data of 20 Hz, the data sampling rate of strainmeter in mainland China is minute sampling due to data storage and transmission technology. Using these minute data, scholars in mainland China have carried out a lot of research, including the tidal Variation and calibration technology (Qiu et al, 2015), abnormal changes of different earthquakes (Qiu et al, 2010;Liu et al, 2014), co-seismic strain steps (Gong et al, 2019;Li et al, 2020), free oscillation of the earth excited by large earthquakes (Tang et al, 2007;Tang et al, 2008;Qiu, 2017), and also studied and analyzed the influence of water level, air pressure, rainfall and other factors on borehole strain, and studied the data processing methods to identify and eliminate these influencing factors (Zhou et al, 2008;Zhang and Huang, 2011;Zhang et al, 2015). However, these studies are limited to longer period signals because of the low sampling rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike GTSM strainmeter such as the United States, which can produce high frequency data of 20 Hz, the data sampling rate of strainmeter in mainland China is minute sampling due to data storage and transmission technology. Using these minute data, scholars in mainland China have carried out a lot of research, including the tidal Variation and calibration technology (Qiu et al, 2015), abnormal changes of different earthquakes (Qiu et al, 2010;Liu et al, 2014), co-seismic strain steps (Gong et al, 2019;Li et al, 2020), free oscillation of the earth excited by large earthquakes (Tang et al, 2007;Tang et al, 2008;Qiu, 2017), and also studied and analyzed the influence of water level, air pressure, rainfall and other factors on borehole strain, and studied the data processing methods to identify and eliminate these influencing factors (Zhou et al, 2008;Zhang and Huang, 2011;Zhang et al, 2015). However, these studies are limited to longer period signals because of the low sampling rate.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the borehole strainmeter can be used for seismic wave observation (Byerly, 1926;Johnston et al, 1986;Borcherdt and Glassmoyer, 1989;Borcherdt et al, 2006;Johnston et al, 2006;Blum et al, 2010;Barbour and Agnew, 2012;Qiu et al, 2015;Barbour and Crowell, 2017;Canitano et al, 2017;Cao et al, 2018;Farghal et al, 2020;Barbour et al, 2021). This initially realized seismologists' expectations of strain seismographs (Benioff et al, 1961;Aki and Richards, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, borehole strainmeters, The associate editor coordinating the review of this manuscript and approving it for publication was Stefania Bonafoni . which detect crustal changes at high resolution on different time scales ranging from seconds to years [11], [12] provide an opportunity to investigate the preparation process prior to earthquakes [13]- [16], slow earthquakes [17], [18], seismic strain steps [19], [20], and volcanic eruptions [21].…”
Section: Introductionmentioning
confidence: 99%
“…The observations have many advantages such as high resolution, broad band, and topographic-feature-independence, amongst others. High-resolution borehole strainmeters allow for the detection of subtle strain variations to study slow earthquakes [Sacks et al, 1978[Sacks et al, , 1981Linde et al,1996;Liu et al, 2009], seismic strain steps [McGarr et al,1982;Asai et al,2005;Qiu et al, 2003Qiu et al, , 2004Qiu et al, , 2015Barbour et al, 2012], and volcanic eruptions [Voight et al, 2006;Hautmann et al, 2013;Sturkell et al, 2013]. 1High-resolution borehole records also provide the opportunity to investigate strain changes prior to earthquakes.…”
Section: Introductionmentioning
confidence: 99%